Proceedings of the 8th ACM International Symposium on Advances in Geographic Information Systems 2000
DOI: 10.1145/355274.355298
|View full text |Cite
|
Sign up to set email alerts
|

Cartography and geographic information systems as semiotic systems

Abstract: Geographic Information Systems (GIS) have grown rapidly, motivated by general trends of information technologies in expanding their potential uses. In line with this tendency, GIS must consider the familiarity of new users with Cartography and their traditional way of representing natural phenomena. This paper evaluates the expressive power of GIS relative to their cartographic elements, based on a Semiotic approach, which is concerned with understanding the construction and interpretation of maps as communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
2
Order By: Relevance
“…Significant barriers to the growth of internet-based geographic tools surround the user's ability to manipulate and interpret geographic information along with software interface usability issues. It is reasonable to assume that non-specialist geographic information users have only a limited knowledge of geographic information (in comparison to geographic specialists) and, therefore, may find the specialist nature of geographic information applications demanding [16]. Therefore, an important attribute of online map tools is their adaptability, especially the ease with which they can be tailored to suit the dynamically changing user demands [17].…”
Section: Digital Maps: Gis and The Internetmentioning
confidence: 99%
“…Significant barriers to the growth of internet-based geographic tools surround the user's ability to manipulate and interpret geographic information along with software interface usability issues. It is reasonable to assume that non-specialist geographic information users have only a limited knowledge of geographic information (in comparison to geographic specialists) and, therefore, may find the specialist nature of geographic information applications demanding [16]. Therefore, an important attribute of online map tools is their adaptability, especially the ease with which they can be tailored to suit the dynamically changing user demands [17].…”
Section: Digital Maps: Gis and The Internetmentioning
confidence: 99%
“…Help users tagging online photos (e.g. flicker) in order to make an effective computation or search activity (Hargood et al, 2010) Improve online help system in order to provide better access to it (Silveira et al, 2001) Assist in understand the construction and interpretation of maps as a communication activity (Prado et al, 2000) Help in collaborative tagging system (Cattuto et al, 2006) Improve the methodological and technological search support in social network service (SNS) (dos JSIT 15,1 Table VI also showed example benefits to each of these categories and total number of papers to each category of benefits. The percent of papers to each category of benefit are shown in Figure 13, which showed that the maximum numbers of papers were focused to achieve the goals related to interface design (43.07 percent) and then the communication goal (20 percent).…”
Section: No Of Papersmentioning
confidence: 99%
“…A research described in (Prado et al, 2000) was based on viewing and interpreting maps as comunication ac-tivities about natural facts of the real world. The main research goal was to evaluate the expressive power (and the expressive limitations) of GIS tools.…”
Section: Related Workmentioning
confidence: 99%